Recurrence Rates Following Arthroscopic Shoulder Stabilization are Improved Following a Criteria Based Return to Sport Testing Protocol - Popchak, Adam (Orthop J Sports Med, 2020)
OBJECTIVES: Recurrent shoulder instability after arthroscopic shoulder stabilization is a challenging complication that often manifests after return to sports. Many physicians use an arbitrary minimum of 5 months from surgery for clearance, although there is little data to support the use of temporal based criteria. Prior literature on ACL reconstruction has demonstrated overwhelming evidence for improved failure rates following return to sport after criteria based testing compared to time based clearance, but no such studies to date have evaluated the use of objective return to play testing protocols on recurrence rates following arthroscopic shoulder stabilization. We have prior presented on a return to sport criteria-based protocol that has demonstrated that a majority of athletes have residual strength and functional limitations which would preclude them from full clearance and return to play at 6 months postoperatively. The purpose of this study is to analyze the impact of a return to play criteria-based testing protocol on recurrent instability following arthroscopic shoulder stabilization. We hypothesized that patients who meet return to play criteria would have less recurrent instability compared to those who did not undergo the testing and were cleared to return based on time from surgery. METHODS: Forty eight patients (group I) who underwent arthroscopic shoulder stabilization surgery from 2016 to 2018 with minimum 1 year follow up and were referred during postoperative rehabilitation for functional testing to evaluate readiness for return to sport were included in this retrospective case controlled study. These patients were compared to a control group of forty-eight historical consecutive cases (group II) who did not undergo return to sports testing and were cleared for sports after a minimum of 5 months following surgery. Patients with critical glenoid bone loss or off-track Hill-Sach’s lesions necessitating a remplissage or bone augmentation procedure were excluded from the study. ANOVA and independent t test were performed to analyze recurrence shoulder instability rates defined as dislocations or subluxation symptoms. RESULTS: There was no difference between groups with regard to age ( p=0.64), sex (p=0.24), hand dominance (p=0.84), or participation in contact sports (p=0.66). Patients who underwent return to play criteria based testing protocol had a statistically significant difference in the rate of recurrent shoulder instability (10% vs. 31%, odds ratio=3.9, p<0.001). CONCLUSION: Athletes who undergo an objective return to play criteria based testing protocol have lower rates of recurrent instability following arthroscopic shoulder stabilization surgery than those cleared by time from surgery. Based on our findings, we strongly recommend the utilization of a criteria based testing protocol for return to play following arthroscopic shoulder stabilization, particularly for sports that have known higher risks of recurrence.